E-Mail-Austausch zwischen Alexandre Pomar und Katharina Greven - Pomar, Alexandre; Greven, Katharina (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2019)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Art; Africa; Artists; Exhibitions; Art Exhibition; Email; Cultural Centre; Performing Arts Center; Art Collector; Art Collecting